Reforestation with Bombacopsis quinatum (Jaq.) Dugand (Bombacaceae) in Costa Rica by means of vegetative reproduction - Hunter, J. Robert (1987)
Bombacopsis quinatum is found in northern South America and in Central America as far north as Honduras. In these areas, this tree is esteemed for its lumber.This paper deals chiefly with the promise of planting this species easily, economically and on a large scale by means of vegetative propagation. Indications are that this technique might serve as a novel system of reforestation, especially in abandoned areas in scrub, second growth or marginal sites such as those under poor pasture management.